The potentials of OCDM technique for local area network - Syed Alwee Aljunid, Syed Junid; Dayang Khadijah, Hamzah; Shariffah Zarihan, Syed Zaharim Helmi; Anuar, Mat Safar; Azremi, Abdullah Al Hadi; Mohamad Khazani, Abdullah (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org